Indices based on silicoflagellate assemblages offer potential for paleo-reconstructions of the main oceanographic zones of the Southern Ocean - Rigual-Hernández, Andrés S.; Trull, Thomas W.; McCartney, Kevin; Ballegeer, Anne Marie; Lawler, Kelly Anne; Bray, Stephen G.; Armand, Leanne K. (Geo-Marine Letters, 2016)
This study reports detailed silicoflagellate assemblage composition and annual seasonal flux from sediment traps at four locations along a transect across the Southern Ocean frontal systems. The four traps sampled the central Subantarctic Zone (SAZ, 47°S site), the Subantarctic Front (SAF, 51°S site), the Polar Frontal Zone (54°S site) and the Antarctic Zone (61°S site) across the 140°E longitude. Annual silicoflagellate fluxes to the deep ocean exhibited a similar latitudinal trend to those of diatom fluxes reported in previous work, with maxima in the Antarctic Zone and minima in the Subantarctic Zone. The data suggest that, along with diatoms, silicoflagellates are important contributors to biogenic silica export at all sites, particularly in the Subantarctic Zone. Two main silicoflagellate genera were observed, with Stephanocha sp. (previously known as Distephanus) dominating polar waters and Dictyocha sp. important in sub-polar waters. This is consistent with previous use of the Dictyocha / Stephanocha ratio to infer paleotemperatures and monitor shifts in the position of the Polar Frontal Zone in the sedimentary record. It appears possible to further refine the application of this approach by using the ratio between two Dictyocha species, because Dictyocha aculeata dominated at the Subantarctic Front, while Dictyocha stapedia dominated in the central Subantarctic Front. Given the well-defined environmental affinities of both species, a new SAF silicoflagellate index (SAF-SI) based on this ratio is proposed as a useful diagnostic for SAF and SAZ water mass signatures in the Plio-Pleistocene and Holocene sedimentary record.